A roman centurion proclaims : I beheld His glory - Wilson, Robert; Mcready, George; Digiview Productions (Digiview Productions, 2004)
Relates the events of Christ's crucifixion through the eyes of a Roman centurion who is converted through this experience.
Title from disc surface.
Originally broadcast on television in 1953.
"Digitally remastered"--Pkg
Keywords: Jesus Christ -- Crucifixion -- Drama